Barriers for the inclusion of sexuality in nursing care for women with gynecological and breast cancer: perspective of professionals (Revista Latino-Americana de Enfermagem, 2015)
AIM: qualitative study, which aimed to identify the barriers that influence nursing care practices related to the sexuality of women with gynecological and breast cancer. METHODS: the study was conducted with 16 professionals of the nursing area (nurses, nursing technicians and nursing assistants) from two sectors of a university hospital situated in the state of São Paulo, Brazil. The data was collected using semi-structured, in-depth individual interviews. All the interviews were recorded and the participants' responses were identified and categorized using Content Analysis. RESULTS: three major themes were identified. These are as follows: 1) barriers related to the biomedical model; 2) barriers related to institutional dynamics and 3) barriers related to the social interpretations of sexuality. CONCLUSIONS: the results of this study showed that the systematized inclusion of this issue in nursing care routines requires changes in the health paradigm and in the work dynamic, as well as reflection on the personal values and social interpretations related to the topic. A major challenge is to divest sexuality of the taboos and prejudices which accompany it, as well as to contribute to the nursing team being more aware of the difficulties faced by women with gynaecological and breast cancer.